Long-Term Consequences of Teaching Gender Roles: Evidence from Desegregating Industrial Arts and Home Economics in Japan - Hiromi Hara; Núria Rodríguez-Planas (Institute of Labor Economics (IZA), 2021)
We explore whether a 1990 Japanese educational reform that eliminated gender-segregated and gender-stereotyped industrial arts and home economics classes in junior high schools led to behavioral changes among these students some two decades later when they were married and in their early forties. Using a Regression Discontinuity (RD) design and Japanese time-use data from 2016, we find that the reform had a direct impact on Japanese women's attachment to the labor force, which seems to have changed the distribution of gender roles within the household, as we observe both a direct effect of the reform on women spending more time in traditionally male tasks during the weekend and an indirect effect on their husbands, who spend more time in traditionally female tasks. We present suggestive evidence that women's stronger attachment to the labor force may have been driven by changes in beliefs regarding men' and women's gender roles. As for men, the reform only had a direct impact on their weekend home production if they were younger than their wives and had small children. In such relationships, the reform also had the indirect effect of reducing their wives' time spent in weekend home production without increasing their labor-market attachment. Interestingly, the reform increased fertility only when it decreased wives' childcare. Otherwise, the reform delayed fertility.
Keywords: J22; J24; I2; 330; junior high school; coeducation of industrial arts and home economics; gender gaps; time-use data; employment and labor income; and fertility